Risk Factors for Bronchopulmonary Dysplasia - Hilal Özkan; Nilgün Köksal; Merih Çetinkaya; Yakup Canıtez (Güncel Pediatri, 2008)
Aim: Bronchopulmonary dysplasia (BPD) is a chronic lung disease that develops in premature infants who were treated with oxygen and positive pressure ventilation. Although there are recent advances in neonatal care, it has been still the most common long term complication in preterm infants. The aim of this study was to evaluate infants who developed BPD throughout the clinical course of hospitalisation and to determine BPD frequency and also the risk factors associated with BPD.Materials and Method: A total of 276 infants who admitted to neonatal intensive care unit between January 2005 and January 2006 were included to this study. The infants with and without BPD were compared according to characteristic features and risk factors.Results: The mean gestational age and birth weight of all infants were 31±3.1(range, 24-36) weeks, and1607±610 (range, 500-4000) gram, respectively. BPD was diagnosed in 30% (84/276) of all infants. The mean gestational age and birth weight of infants with BPD were 30±3 (range, 24-36) weeks, and 1171±423 (range, 530-3700) gram, respectively. The 36% (31/84) of infants were smaller than 28 gestational age and 41.9% (26/84) were smaller than 1000 gram. Gestational age and birth weight were found to be the most important risk factors for development of BPD, and BPD risk increased as the gestational age and birth weight decreased. The duration of mechanical ventilation in infants with BPD and without BPD were found to be 40±4.3 days and, 17±2 days, respectively and this difference was found to be statistically significant (p<0.05). Similarly, the duration of oxygen therapy was found to be statistically higher in infants with BPD compared with the infants without BPD (p<0.05). Also, respiratory distress syndrome, intraventricular hemorrhage, chorioamnionitis in mother, prolonged total parenteral nutrition, and frequent blood transfusion were also other risk factors that were significantly associated with development of BPD. Conclusion: The risk for BPD is multifactorial. It was observed that the most important risk factors for BPD were prematurity, low birth weight, mechanical ventilation and prolonged oxygen therapy. Preventing small gestational age and low birth weight prematurity, decreasing the duration of mechanical ventilation and also to give minimum oxygen supply in premature infants. (Journal of Current Pediatrics 2008; 6: 66-71)